Phytochemical studies on traditional medicinal plants with antimalarial activities - Chen, Dianne Tzu-Hsiu (Department of Chemistry, 2016)
The active antimalarial principles of three traditional medicinal plants, Passerina obtusifolia (Thymelaeaceae), Tetradenia riparia (Labiatea) and Xerophyta retinervis (V elloziaceae) were investigated by employing bioassay guided fractionation. Two novel compounds and five known constituents were isolated from the active fractions of these three plants. The types of compounds isolated included: three triterpenoids (20(29)-Lupene-3α,28- diol (30), 20(29)-Lupene-3α, 16β,28-triol (32) and 3β-Hydroxy-20(29)-Lupen-28-oic acid (42)); two diterpenoids (8-Abietene-7 β,13 β -diol (45) and cariocal (51)); one flavonoid ( 5-Hydroxy:.4' ,6, 7-trimethoxyflavone ( 44)) and one flavonolignan ( 11-0- acetyl hydnocarpin (62)). In addition, one analogue of 7α-hydroxyroyleanone (41) (which was previously isolated from T riparia and was found to be the active antimalarial principle of the plant) was prepared.